The Role Of Work-Life Balance In Mediating The Effect Of Work Flexibility And Self-Efficacy On The Performance Of Independent Property Agents In Tabanan Regency Bali - Adi Putra Wijayantara; Sutoyo; Koen Irianto Uripan; Sutomo; Immanuel Ustradi Osijo (International Humanity Advance, Business & Sciences, 2026)
The phenomenon of independent work, especially in the field of property agents, is experiencing significant growth, but independent property agents face special challenges in managing their time and performance. Optimal performance is influenced by a high level of work flexibility and a strong sense of self-efficacy. This study aims to analyze and empirically test the role of work-life balance (WLB) as a mediator that mediates the influence of work flexibility and self-efficacy on the performance of independent property agents in Tabanan Regency, Bali. The method used is quantitative with an explanatory design. The study population includes independent property agents operating in Tabanan Regency. The sample was taken by convenience/purposive sampling technique, resulting in 80 respondents. Data was obtained through questionnaires distributed online and offline, then analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the help of SmartPLS software. The results show that work flexibility and self-efficacy have a positive and significant effect directly on the performance of independent property agents. In addition, work-life balance is a partial or full mediator in the relationship between flexible work and self-efficacy with performance. In particular, the high flexibility of work allows agents to achieve a better work-life balance, which further improves their performance. Similarly, a high level of self-efficacy is positively associated with a good work-life balance, which in turn strengthens performance. This study makes a theoretical contribution by combining the concepts of work flexibility, self-efficacy, work-life balance, and performance in the context of independent property agents. In practical terms, these findings suggest that companies or property agent management teams focus on: 1) Maintaining and expanding work autonomy (flexibility); 2) Organizing training to increase self-efficacy; and 3) Building a culture that supports work-life balance as the main strategy to optimize the performance of independent property agents in Tabanan, Bali.